Penerapan online & offline marketing terstruktur serta perbaikan desain kemasan guna meningkatkan daya saing UMKM King Keripik di Kabupaten Batang - Alpin Hidayatulloh Hidayatulloh; Rita Dewi Kristiana; Aziz Prabowo; Andre Geza H; Iffah Muflihati; Sari Suhendriani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
MSMEs have an important role in various aspects, both economic, social, and cultural, in the lives of Indonesian people. However, some MSMEs such as the “King Keripik” MSME in Batang Regency still have some shortcomings in the marketing, packaging, and labeling systems. Based on these various shortcomings, it is necessary to assist to improve the quality of these MSMEs. The method used is through focus group discussion activities, conducting interviews with MSME owners, marketing strategy assistance, as well as packaging and labeling assistance. The outputs or results obtained include structured online and offline marketing systems obtained products with K-Pack packaging with a layer of aluminum foil on the inside, attractive labeling that has been adjusted to product labeling rules.